Governing A.I.’s Professional Advice - Haupt, Claudia (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2019)
How should we govern professional advice given by artificial intelligence (AI)? The traditional professional-client or doctor-patient relationship is governed by a specific set of legal rules that constitute the legal framework of professional advice-giving. The goal of this legal framework is to ensure the client or patient receives reliable, comprehensive, and accurate advice in order to make important life decisions. But such a regime does not exist when AI gives professional advice. This article suggests that the first step in regulating professional AI should be to turn to the existing framework that regulates professional advice-giving. In focusing on the professional-client relationship, it foregrounds the regulatory access points at which the law can achieve the goal of ensuring good advice, whether rendered by humans or AI.